Implementation of IoT in Shallot Farming in Nganjuk to Increase Production - Atasa, Dita; Agussalim; Anggraeny, Fetty Tri; Maulana, Hendra; Alfiani, Fina (Pascasarjana Universitas Mataram, 2025)
The El Nino phenomenon in 2023 caused more than 50% of Shallot farmers in Pandean Village, Nganjuk Regency, to experience crop failure due to limited water and a weak data-based management system. The target of this community service is 30 shallot farmers who are members of the P4S Santosa Jaya group. This community service activity aims to increase farmers' understanding of the application of the Internet of Things (IoT) in shallot cultivation through socialization, training, and farmer assistance. The implementation method includes preparation, interactive socialization with pre-tests and post-tests, as well as evaluation of farmers' perceptions. The results of the activity show a significant increase in knowledge, where before the activity 50% of participants were in the less knowledgeable category, and after the activity, it increased to 50% in the knowledgeable category and 26.7% in the very knowledgeable category. In addition, farmers' perceptions of IoT are largely positive (50%), although there are still neutral (30%) and skeptical (20%) responses regarding investment costs, internet access, and technical skills. These findings demonstrate that educational assistance can enhance agricultural digital literacy while serving as a first step toward data-driven farming adoption.